Thermogravimetric analysis of agricultural residue carbonized briquettes for domestic and industrial applications - Yiga, Vianney Andrew; Lubwama, Michael (MRS Advances, 2020)
For a material to be used as energy, understanding its combustion behavior is crucial. Biomass is one such material that is increasingly gaining traction. Biomass may be utilized by direct combustion or transformation into fluid or solid biomass-based fuels. In this work, slow pyrolysis of groundnut shells, bagasse, rice husks and coffee husks was done to produce briquettes with cassava starch binder. Thermogravimetric analysis (TGA) was carried out using an Eltra Thermostep thermogravimetric analyzer. The samples were heated from ambient to 920 deg. Celsius. This analysis provided combustion explanations in terms of the weight loss, burning rates, peak temperatures, char residues and mean reactivity. TGA results showed that binder inclusion reduced the amount of fixed carbon present in the developed briquettes, thus slightly reducing their calorific values. Rice husks briquettes yielded the least weight loss (20.9% and 24.7% for 30g and 50g binder incorporations respectively) compared to others, owing to former’s higher ash contents. Increase in binder contents reduced the amount of char residues, caused by reducing ash contents in the developed briquettes. Peak temperatures and char residues generally increased with increasing binder content. This signifies increasing thermal stabilities of the developed briquettes. Highest char residues were obtained by briquettes developed with rice husks at 30g binder while briquettes developed with bagasse briquettes developed at 50g binder had the least char residues. The highest mean reactivities were obtained in briquettes developed from bagasse and coffee husks while briquettes developed from rice husks had lowest mean reactivities. Briquettes developed in this study showed sufficient combustion properties suitable to provide energy for domestic and industrial applications.
Keywords: Thermogravimetric analysis; Agricultural residue; Carbonized briquettes; Domestic and industrial applications